Autism and the community a design for living in transition - Jimenez, Jose Raoul P.; Yazon, Rizalino III O. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
In the research and design of this thesis, an agenda-based approach was applied wherein a facility is to be programmed and designed based on the perceived site-based issues. Using this approach, the chosen neighborhood-scale site- Molino II & III Bacoor, Cavite was analyzed and the main issues were identified to be the lack of community centered spaces and a social disconnection within the community. This led to a two-part agenda: fostering community ties and empowering persons with autism. The Persons With Autism (PWA) sector was chosen as the social group that could be the anchor of a community project as cases of Autism are growing in this area in particular wherein support for disadvantaged sectors of the community remains a mere goal. The resulting hybrid facility is a 24-hour transitional living center for adults with Autism cross-integrated with a community activity center. In the design of this particular center, the main problem to be explored is, "how can living, learning, and social spaces be designed to help adults with Autism be more independent?" Through the exploration of different prevailing theories and concepts in community design and designing for persons with Autism, a final working facility was produced addressing the design problem and, ultimately, the set agenda rooting from the chosen neighborhood.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman